PENGARUH HALAL LABEL DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN WARDAH PADA GENERASI-Z - Khadijh Maulina Andhini, - (2022)
This research is based on the phenomenon of cosmetic industry in Indonesia that is increasing globally and nationally, as well as the dominance of Gen Z as a population in Indonesia as much as 27.94% of the population that uses cosmetic products in their daily lives, especially Wardah. The huge escalation is not accompanied by Gen Z awareness of halal label on product packaging, as well as the brand image of Wardah cosmetic products. The purpose of the study was to find out if halal labels and brand images influence the interest in purchasing decisions on Wardah cosmetic products. The population in this study are consumers who used Wardah cosmetic products at least once in a one year or using this product. The sampling technique used is non probability sampling with the type of purposive sampling sample as many as 213 people. The method used in this study is the causality method with quantitative approach, which is analyzed with Partial Least Square-Structural Equation Modeling (PLS-SEM). The results showed that halal label and brand image have positive and significant influence on the decision to purchase Gen Z in Wardah cosmetic products. This research is expected to provide benefits to companies in understanding consumers about the importance of maintaining halal label on product packaging.